Pengaruh Job Enricment, Loyalitas dan Tekanan Kerja Terhadap Kinerja Pegawai - Situmorang, Abdi Jusandi; Siregar, Adinda Maya Sari; Wahyuni, Sri; Wirasini, Wirasini; Lase, Wetiani; Safrida, Safrida; Nasti, Nilawati; Supriadi, Supriadi (Graha Mitra Edukasi, 2024)
This study aims to determine the Effect of job enrichment, loyalty and work pressure partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Belawan. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Belawan Jalan KL Yos Sudarso Km 8,2 Nomor 27 Medan, with a population of 98 people, and a study sample. of 96 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained job enrichment have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by the results of t count analysis > t-table (9,697 > 2,011) at n = 96 at 95% significance level. Loyalty has a not effect on the performance of employees work of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count > t-table (3,035 > 2,011) at n = 96 at 95% significance level. Work pressure has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by an analysis of t count <-table (1,614 < 2,011) at n = 96 with a significant level of 95%.Value of F-count> F table (62,449 > 2,70) This states that together (multiple) there are positive and significant effects of job enrichment, loyalty and work pressure on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Belawan. Thus the hypothesis proposed is accepted by the truth.